The Characterization of a Human Disease-Associated Mutation Nkx2.5 R142C Using In vitro and In vivo Models - Zakariyah, Abeer (Université d'Ottawa / University of Ottawa, 2017)
Nkx2.5 is a cardiac transcription factor that plays a critical role in heart development. In humans, heterozygous mutations in the NKX2.5 gene result in congenital heart defects (CHDs), but the molecular mechanisms by which these mutations cause the defects are still unknown. NKX2.5 R142C is a mutation that is found to be associated with atrial septal defect and atrioventricular block in 13 patients from one family. The R142C mutation is located within both the DNA-binding domain and the nuclear localization sequence of NKX2.5 protein. The pathogenesis of CHDs in humans with R142C point mutation is not well understood. Also, a previous study in our laboratory has identified Mypt1/PP1 as a novel interacting partner of Nkx2.5 in stem cells during cardiomyogenesis. Nkx2.5 has a PP1-binding consensus sequence RVxF located in the N-terminus of the homeodomain. Notably, the PP1-binding sequence, RVxF, is mutated from arginine to cysteine in patients with the R142C heterozygous mutation. However, the ability of the R142C mutation to bind to the Mypt1/PP1 complex has not been investigated yet. The following thesis addresses the functional deficit associated with R142C by utilizing a combination of in vitro, and in vivo models. It also addresses the interaction of Mypt1/PP1 with the R142C mutation. We have generated a heterozygous mouse embryonic stem cell (mESC) line, harboring the murine homologue (R141C) of the human mutation R142C in Nkx2.5 gene. We show reduced cardiomyogenesis and impaired subcellular localization of Nkx2.5 protein in Nkx2.5R141C/+ mESCs. Gene expression profiling of Nkx2.5R141C/+ mESCs revealed a global misregulation of genes important for heart development and identified putative direct target genes of Nkx2.5 that are affected by the R141C heterozygous mutation. We also generated a mouse model harboring the human mutation R142C. We show that the Nkx2.5R141C/R141C homozygous embryos are developmentally arrested around E10.5 with delayed heart morphogenesis. Moreover, Nkx2.5R141C/+ newborn mice are grossly normal but show variable cardiac defects and downregulation of ion channel genes that later cause AV block in adult mice. Finally, we show that the R141C mutant binds to the Mypt1/PP1 complex but is not inhibited or translocated to the perinuclear region in the presence of Mypt1/PP1 as the WT Nkx2.5 is.
Keywords: Transcription factors; Congenital heart defects; mouse embryonic stem cells; cardiac muscle differentiation